PENERAPAN EVIDENCE BASED NURSING EFEKTIFITAS TERAPI BERMAIN MEWARNAI GAMBAR TERHADAP KECEMASAN ANAK DENGAN HOSPITALISASI - Carennina Clara Dita; Rokhaidah (AKPER Pasar Rebo, 2018)
Hospitalization in children can cause anxiety and stress at all age levels. One of the efforts to lower the anxiety play therapy colouring pictures. This research aims to know the existence of the play therapy influences colouring pictures against anxiety in children hospitalization. This research method using quasy experiments with one group pretest posttest design. Data collection using the questionnaire Hamilton Rating Scale for Anxiety (HAR-S) the determination of the sample using a purposive sampling with a total of 24 respondents. The results of the statistical test for paired samples t-test p value 0.000 results obtained (p value < α 0.05) so that it can be concluded that there is a therapeutic influence drawing against anxiety in children hospitalization. The study suggested granting therapy colouring pictures in children with hospitalization as an effective way to decrease anxiety.